Taxonomic status of Apostolepis barrioi Lema, 1978, with comments on the taxonomic instability of Apostolepis Cope, 1862 (Serpentes, Dipsadidae) - Entiauspe-Neto, Omar Machado; De Sena, Arthur; Tiutenko, Arthur; Loebmann, Daniel (ZooKeys, 2019)
Apostolepis is a diverse neotropical snake genus, which has been historically subjected to poor taxonomic descriptions, largely based on either a small type series or subjective diagnoses. We evaluate the case of Apostolepis barrioi Lema, 1978 and its intricate taxonomic history, suggesting its synonymization with Apostolepis dimidiata (Jan, 1862), and providing brief commentary on the taxonomic instability that has been plaguing the genus.
CRIS-Team WoS Importer:2019-05-09